KEISLAMAN DAN ETIKA KEILMUAN: TELA’AH PEMIKIRAN KH. M. HASYIM ASY’ARI - Lukman, Maman (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
Islam is a system of values, guidelines, and regulations from Allah SWT that were specifically revealed to the Prophet Muhammad SAW for the welfare, safety, and peace of humanity and the universe. This system of values and rules covers how to establish relationships with Allah, fellow human beings, and the universe. And the scientific ethics are manners, morals, etiquette, or the Operational Procedures System, which is one of the important software instruments, and its existence is vital to achieving the goals of Islamic Education. This journal uses a literature review method, examining the thoughts of KH.M.Hasyim Asy'ari in the book Adab al-Alim wa al-Muta'alim, written in 1923, regarding Islam and scientific ethics. Islamic thought and scientific ethics are presented with descriptive analysis. This study shows that KH.M. Hasyim Asy'ari's Islamic thoughts are characterized by traditional Indonesian Islam, which focuses on the Sufism of Al-Junaidi Al-Baghdadi and Imam Al-Ghazali, Theology (ahlussunah wal jama'ah) Abu Hasan Al-Asy'ari and Abu Mansur Al-Maturidi, and adherents of the four schools of fiqh and national syiasah fiqh. KH.M. Hasyim As'ari's thoughts contain scientific ethics covering two aspects, namely ethics for educators and students. According to him, the goal of education for every human being is to become a perfect human being, in order to get closer to the Creator, in order to achieve happiness in this world and the hereafter. In the book Adab al-Alim wa al-Muta'alim, it is stated that ethical values must be a grand design for everyone (educators and students) or for all people. Thus, a seeker of knowledge embodies his knowledge in his daily life through behavior that is tawakkal (trust in God), wara' (restraint), doing good deeds with the sole intention of seeking God's pleasure, gratitude, and sincerity